Role of CXCL10 released from osteocytes in response to TNF-α stimulation on osteoclasts - Mariko Miura; Hideki Kitaura; Fumitoshi Ohori; Kohei Narita; Jiayi Ren; Takahiro Noguchi; Aseel Marahleh; Jinghan Ma; Angyi Lin; Ziqiu Fan; Itaru Mizoguchi (Scientific Reports)
Abstract Tumor necrosis factor-alpha (TNF-α) is a significant cytokine that regulates bone resorption under inflammatory conditions. However, its mechanism of action in osteocytes remains unclear. In this study, highly purified osteocytes were isolated from dentin matrix protein 1 (DMP1)-Topaz mice using cell sorter. RNA sequencing (RNA-seq) revealed that TNF-α stimulation increased C-X-C motif chemokine ligand 10 (CXCL10) gene expression in osteocytes. Although CXCL10 did not affect osteoclast differentiation in vitro, it enhanced the migration of osteoclast precursors. Additionally, in the transwell co-culture system, TNF-α induced the migration of osteoclast precursors. However, this effect was attenuated by a CXCL10-neutralizing antibody. In vivo, mice were administered supracalvarial injections of TNF-α with or without the CXCL10-neutralizing antibody for 5 days. The percentage of CXCL10-positive osteocytes increased after TNF-α administration. Additionally, osteoclast formation and bone resorption were assessed. CXCL10-neutralizing antibody-treated calvariae exhibited a significantly lower number of osteoclasts and bone resorption than those treated with TNF-α alone. These results indicated that TNF-α-induced CXCL10, which affects the migration of osteocyte-derived osteoclast precursors, may enhance TNF-α-triggered osteoclast formation and bone resorption in vivo.